Gender, Social, Cultural Injustice in the Short Story “Di Atas Tanah Retak” and the Lesson Plan - Sulistyaningrum, Caecilia Fani; Dewi, Novita (Raja Zulkarnain Education Foundation, 2025)
This study aims to describe: 1) gender, social and cultural injustice in the short story